A MODEL FOR TEACHING INFORMATICS TO PRIMARY SCHOOL STUDENTS BASED ON ELECTRONIC HIERARCHICAL STRUCTURES - Kaldanov Б.Б.; Bidaibekov Е.Ы. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
This article shows that the digitalization of education requires a systematic approach to organizing the content of the informatics course in primary school. The relevance of the study lies in the need to develop a pedagogically grounded teaching model based on electronic hierarchical structures. The purpose of the research is to design an original instructional model that provides structured, adaptive, and visual delivery of content, taking into account the cognitive characteristics of younger learners. The study utilized methods of analyzing national and international experiences in teaching informatics, comparing the conceptual framework of V.V. Grinshkun’s model with Bloom’s taxonomy levels, as well as techniques of computer modeling and computational experimentation. As a result, an original three-level teaching model was proposed and implemented in a new information integrator. The validation of the model based on Bloom’s taxonomy and the findings from the computational experiment confirmed the cognitive coherence, pedagogical soundness, and high adaptability of the developed structure. The study substantiates the effectiveness of applying electronic hierarchical structures to optimize informatics education in primary school. Future prospects include the development of the model into an adaptive learning system using digital platforms and artificial intelligence.